2019
DOI: 10.3892/ol.2019.10566
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RUNX3 gene and miR-363 in colorectal cancer and the relationship with clinicopathological features

Abstract: Expression of RUNX3 gene and miR-363 in colorectal cancer was studied to explore its relationship with clinicopathological characteristics of colorectal cancer and to analyze the value of RUNX3 combined with miR-363 in the diagnosis of colorectal cancer. In total, 85 patients diagnosed with colorectal cancer in the First Peoples Hospital of Xiaoshan Hangzhou from March 2014 to July 2016 were the experiment group. Seventy healthy individuals who underwent physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…After verification, it was observed that miR-363 exhibited the most significant down-regulation in SNK-6 and HANK1 cells, suggesting the involvement of miR-363 in NKTCL. According to previous studies, miR-363 is a typical and effective tumorsuppressor gene in cancer (44,45), which is consistent with our research. Furthermore, miR-363 has been indicated to regulate SQLE that is significantly related with tumor immune cell infiltration and checkpoints in pancreatic adenocarcinoma (46).…”
Section: Discussionsupporting
confidence: 93%
“…After verification, it was observed that miR-363 exhibited the most significant down-regulation in SNK-6 and HANK1 cells, suggesting the involvement of miR-363 in NKTCL. According to previous studies, miR-363 is a typical and effective tumorsuppressor gene in cancer (44,45), which is consistent with our research. Furthermore, miR-363 has been indicated to regulate SQLE that is significantly related with tumor immune cell infiltration and checkpoints in pancreatic adenocarcinoma (46).…”
Section: Discussionsupporting
confidence: 93%
“…9 The RUNX3 can be used as a basis for judging the degree of malignancy of CRC and is an indicator for the assisted diagnosis of this neoplasm. 10 Furthermore, RUNX3 expression is frequently reduced in human intestinal metaplasia; polymorphisms within RUNX3 have been reported in digestive cancers such as gastric cancer. [11][12][13] This fact raised the possibility that genetic polymorphisms within the functional region of RUNX3 would lead to aberrant expression and further confer a risk for CRC.…”
Section: Introductionmentioning
confidence: 99%